EFFECTIVENESS OF ANTIBIOTICS IN TREATMENT OF ADULT PNEUMONIA AT DONG NAI GENERAL HOSPITAL (Vietnam Journal of Community Medicine, 2022)
Objectives: To describe the effectiveness of antibiotic in treatment of adult pneumonia at Dong NaiGeneral Hospital in 2021.Subjects and methods: A prospective, descriptive study of 114 patients diagnosed pneumonia andtreated at Dong Nai General Hospital from September the 1st, 2020 to March the 1st, 2021.Results: 81.58% of study patients responded well to antibiotics, the success rate in the group using2 antibiotics was 82.02% and 3 antibiotics was 100.0%. The difference in success rate betweengroups using different treatment regimens was statistically significant with p = 0.018. Patients whoboth changed antibiotics and added antibiotics had the highest success rate, accounting for 100.0%,patients who had to change antibiotics and patients who were supplemented with antibiotics had thesuccessful rate were 83.33% and 87.50%, respectively. This difference was significant with p
Keywords: Effectiveness of antibiotics, adult pneumonia.